Developing Data to Support Effective Coordination of Nonprofit Hospital Community Benefit Investments. Issue 4 (July 2018) - Baehr, Avi; Doty, Amanda M. B.; Karp, David N.; Rising, Kristin L.; Carr, Brendan G.; Powell, Rhea E.
Abstract : EXECUTIVE SUMMARY: Nonprofit hospitals achieve tax exemption through community benefit investments. The objective of this study was to characterize urban and suburban nonprofit hospitals' community benefit expenditures and to estimate regional per capita community benefit spending relative to community need. Community benefit expenditures, both overall and by subtype, were compared for urban versus suburban nonprofit hospitals in a large metropolitan area, the greater Philadelphia region. Estimated zip code–level per capita expenditures were mapped in the urban core area. We found that urban hospitals report higher overall community benefit expenditures than suburban hospitals yet invest less in community health improvement services, both proportionally and absolutely, despite spending similar proportions on charity care. There is an overlap in hospital-identified community benefit service areas in the urban core, but the degree of overlap is not related to community poverty levels. There is significant variation in zip code–level per capita community benefit expenditures, which does not correlate with community need. Community benefit investments offer the potential to improve community health, yet without regional coordination, the ability to maximize the potential of these investments is limited. This study's findings highlight the need to implement policies that increase transparency, accountability, and regional coordination of community benefit spending. Abstract : Supplemental Digital Content is available in the text